The Changing Face of Dentistry: Perspectives on Trends in Practice Structure and Organization. (October 2022) - Atchison, K.A.; Fellows, J.L.; Inge, R.E.; Valachovic, R.W.
An expert panel on trends in dental practice structure and organization was convened as part of the University of Washington Continuing Dental Education program entitled "The Changing Face of Dentistry." This article presents the results of the authors' perspectives related to the ongoing trends in these areas; the ways in which events in the previous year, including the COVID-19 pandemic, had modified these trends; and the ways in which dentistry should respond to these trends. Knowledge Transfer Statement: This perspective is intended to stimulate thoughts by clinicians, researchers, and educators about needed trends to the dental profession. With consideration of changes needed within the dental profession, improvements and implementation of diagnostic coding and value-based care could result in improved oral health for numerous Americans.